2013
DOI: 10.1037/a0031808
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative risk and child development.

Abstract: Childhood multiple risk factor exposure exceeds the adverse developmental impacts of singular exposures. Multiple risk factor exposure may also explain why sociodemographic variables (e.g., poverty) can have adverse consequences. Most research on multiple risk factor exposure has relied upon cumulative risk (CR) as the measure of multiple risk. CR is constructed by dichotomizing each risk factor exposure (0 = no risk; 1 = risk) and then summing the dichotomous scores. Despite its widespread use in developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

89
1,458
6
43

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,466 publications
(1,596 citation statements)
references
References 246 publications
89
1,458
6
43
Order By: Relevance
“…It is considered that this result occurred due to little variation among the districts with regard to the outcomes obtained through the Denver II. In summary, this results of this study corroborate previous study indings that show evidence that biological and environmental factors related to poverty interactively and cumulatively in luence childhood development (1,2,5,10).…”
Section: Half Of the Population Living Of This Metropolis Livesupporting
confidence: 92%
See 1 more Smart Citation
“…It is considered that this result occurred due to little variation among the districts with regard to the outcomes obtained through the Denver II. In summary, this results of this study corroborate previous study indings that show evidence that biological and environmental factors related to poverty interactively and cumulatively in luence childhood development (1,2,5,10).…”
Section: Half Of the Population Living Of This Metropolis Livesupporting
confidence: 92%
“…In recent decades studies have aimed to investigate the impact of multiple risk factors on childhood development, with poverty being among the most discussed and investigated (1,2,3). The indings suggest that the delay in neuropsychomotor development (NPMD) occurs with greater frequency and severity when children live in extreme poverty and for a longer period of life (4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies consistently find that the number of childhood risk factors or “adverse childhood experiences” predict adverse outcomes—including the likelihood of developing a mental disorder in adulthood 38, 39, 40, 41, 42, 43, 44. This association is well described in the Adverse Childhood Experiences study 3, 4, 5, 6.…”
Section: Methodsmentioning
confidence: 83%
“…The research in the past two decades has confirmed the importance of establishing supportive environments conducive to brain development and learning opportunities (Pennsylvania Partnerships for Children, 1998;Young, 2015). The home environment, including the range of parenting behaviors and practices, directly affects the likelihood of children developing behavioral problems or, conversely, of protecting children against adverse outcomes (Evans, Li and Whipple, 2013;Fanti and Henrich, 2010;Laurens et al, 2017;Mendel, Tomasello and Nochajski, 2012). To help elaborate further on these variable situations, the concept of "socially toxic environments" refers to the constellations of harsh living conditions that place individuals at significant risk for developmental problems.…”
Section: Socially Toxic Environmentsmentioning
confidence: 99%